A strategy for introducing biopotency-enhanced chirality coating on bio-magnesium - Yu Zhao; Wenjiang Huang; Delin Ma; Qichao Zhao; Xiaxin Qiu; Jinying Liu; Chuanliang Feng; Shaokang Guan (Materials & Design)
Biomedical magnesium alloys (Mg) are often considered potential metallic materials for bone repair scaffolds due to their excellent biomechanical properties, biocompatibility, and biodegradability. However, their rapid degradation behavior is insufficient to support the rapid growth and repair of living tissues. The new surface modification methods to slow down the degradation rate of Mg scaffolds and promote the rapid growth of living tissues is urgent. Here, we developed a chiral-enhanced composite functional coating on the surface of biomedical magnesium. Specifically, a chiral supramolecular hydrogel with graphene oxide (GO) was used to simulate the chiral environment of biological systems, enhancing the adsorption of osteogenic growth factors. Additionally, the silane layers cleverly crosslink traditional silane chains with supramolecular chiral fibers through a hydrogen bond network, which allows the bonding strength (critical loads) of the composite coating to be maintained between 245–275 mN and retains structural integrity when soaked in SBF for 7 days. It was found that both MC3T3-E1 cells growth and BMP-2 adhesion were significantly enhanced by GO-added left-handed chiral coatings, which exhibit superior bone growth-promoting effects. In summary, incorporating chiral features into functional coatings represents a transformative approach in the design and application of bone defect repair materials.